Wonton terror - Chien, Vivien (Chien, Vivien. Noodle shop mystery., 2019)
Lana Lee is all smiles when the first evening of Cleveland<U+2019>s Asian Night Market kicks off the summer. The weekly festival is always good for business, packed with locals and tourists, and this year, some stiff new food-truck competition. Wonton on Wheels, run by old friends of Lana<U+2019>s parents, promises to have customers lining up for their delicately wrapped delights<U+2015>until the truck blows up at evening<U+2019>s end. Lana<U+2019>s boyfriend, Detective Adam Trudeau, had been planning a birthday getaway for the two of them but, lo and behold, Lana must assume the role of amateur sleuth yet again. With one proprietor of Wonton on Wheels dead, it<U+2019>s beginning to look more like murder and less like an unfortunate accident. And as they begin to unwrap layers of disturbing secrets, Lana<U+2019>s own family erupts into new drama. Will Lana be able to solve this crime<U+2015>or has she jumped from the wok right into the fire?